A new approach to railway track switch actuation: Dynamic simulation and control of a self-adjusting switch. (August 2020) - Dutta, Saikat; Harrison, Tim; Ward, Christopher Patrick; Dixon, Roger; Scott, Tara
The track switch is one of the key assets in any railway network. It is essential to allow trains to change route; however, when it fails, significant delays are almost inevitable. A relatively common fault is 'loss of detection', which can happen when there is a gradual track movement and the switch machines (actuators) no longer close the gap between the switch rail and stock rail to within safe tolerance levels. Currently, such misalignment is mitigated by a preventative programme of inspection and manual re-adjustment. In contrast to many other industries, the actuators are exclusively operated in open loop, with sensors (often limit switches) mainly being used for detection. Hence, an opportunity exists to investigate the closed loop control concepts for improving the operation of the switch. This paper proposes two advances: first, a novel approach is taken for modelling the dynamic performance of track switch actuators and the moving permanent-way components of the switch. The model is validated against real data from an operational switch. Secondly, the resulting dynamic model is then used to examine the implementation of closed loop feedback control as an integral part of track switch actuation. The proposed controller is found to perform well and offers the potential of 'self-adjustment', i.e. re-adjusting itself to close any gap (within a predefined range) between the stock and switch rails, thereby completing the switching operation.